An Analysis of Lexical Relations on Lewis Carroll’s Alice in Wonderland - Yuyun Ariska; Wiwin Indiarti; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2020)
The objective of the research is to know the type of lexical relations in Lewis Carroll’s Alice in Wonderland and the most dominant of lexical relation found in the same work. To achieve the objectives, the researcher employs descriptive qualitative method by collecting the randomly sentences of the novel chosen. After collecting and selecting the data, the researcher starts to analyze the words in the sentences by using the theory of lexical relation related to Semantics. The results show that in Lewis Carroll’s Alice in Wonderland there were 65 utterances of lexical relations. They are 17 utterances of synonyms, 13 utterances of homonym, 5 utterances of hyponyms and 30 utterances of antonyms. It is 17 words of synonyms, 13 words of homonym, 5 words of hyponyms and 34 words of antonyms. By having adequate knowledge on lexical relations, any readers can easily understood the words usage. Furthermore, the researcher finds antonym as the most dominant type, whereas hyponym is the lexical relation type with the least case.